Human leucocyte antigen class I‐redirected anti‐tumour CD4+ T cells require a higher T cell receptor binding affinity for optimal activity than CD8+ T cells. (14th November 2016) - Tan, M. P.; Dolton, G. M.; Gerry, A. B.; Brewer, J. E.; Bennett, A. D.; Pumphrey, N. J.; Jakobsen, B. K.; Sewell, A. K.
Summary: CD4 + T helper cells are a valuable component of the immune response towards cancer. Unfortunately, natural tumour‐specific CD4 + T cells occur in low frequency, express relatively low‐affinity T cell receptors (TCRs) and show poor reactivity towards cognate antigen. In addition, the lack of human leucocyte antigen (HLA) class II expression on most cancers dictates that these cells are often unable to respond to tumour cells directly. These deficiencies can be overcome by transducing primary CD4 + T cells with tumour‐specific HLA class I‐restricted TCRs prior to adoptive transfer. The lack of help from the co‐receptor CD8 glycoprotein in CD4 + cells might result in these cells requiring a different optimal TCR binding affinity. Here we compared primary CD4 + and CD8 + T cells expressing wild‐type and a range of affinity‐enhanced TCRs specific for the HLA A*0201‐restricted NY‐ESO‐1‐ and gp100 tumour antigens. Our major findings are: (i) redirected primary CD4 + T cells expressing TCRs of sufficiently high affinity exhibit a wide range of effector functions, including cytotoxicity, in response to cognate peptide; and (ii) optimal TCR binding affinity is higher in CD4 + T cells than CD8 + T cells. These results indicate that the CD4 + T cell component of current adoptive therapies using TCRs optimized for CD8 + T cells is below par and that there is room for substantial improvement. Abstract : Since both CD4+ and CD8+ T‐cell responses are believed to be beneficial for tumour clearance, it could be advantageous to include HLA‐I‐redirected CD4+ T‐cells in adoptive cell transfer regimes in addition to CD8+ T‐cells. Comparison of primary CD4+ and CD8+ T‐cells expressing wildtype and a range of affinity‐enhanced TCRs specific for the HLA A*0201‐restricted NY‐ESO‐1‐ and gp100 tumour antigens shows that redirected primary CD4+ T‐cells expressing TCRs of sufficiently high affinity exhibit a wide range of effector functions, including cytotoxicity, in response to cognate peptide; and that optimal TCR binding affinity is higher in CD4+ T‐cells than CD8+ T‐cells. Our results suggest that the most beneficial therapy might involve engineered CD4+ and CD8+ T‐cells expressing different TCRs with the appropriate TCR:pMHC affinities to allow optimal, synergistic function of both T cell subsets.